Manajemen Pembelajaran Kontekstual Berbasis Ekologi di PAUD: Tinjauan Literatur Terhadap Praktik dan Implikasinya - Nurlina, Nurlina; Meirawan, Danny; Triatna, Cepi; Suyadi, Suyadi (UIN Sultan Maulana Hasanudin Banten, 2025)
Ecological-based contextual learning management in early childhood education is an approach that emphasizes the child's direct involvement with the environment as a learning resource. This approach is believed to be able to improve critical thinking skills, creativity, and environmental awareness from an early age. This study aims to review the practice and implications of ecology-based learning in PAUD through a literature review. The selection of literature sources is carried out based on credibility and relevance, including indexed journals, academic books, and research reports from databases such as Google Scholar and Dimensions . The results of the study show that this approach is effective in forming children's characters who are independent and responsible for the environment, as well as improving their social and emotional skills. However, obstacles such as limited facilities and teachers' lack of understanding of ecopedagogy are still challenges. Therefore, it is necessary to strengthen the capacity of teachers, develop supportive school policies, and collaborate with communities and the government.